Análise histológica e histométrica do efeito do resveratrol em ratos submetidos a periodontite experimental - Rigo Junior, Darlan (2017)
This study aimed to evaluate the effect of RESV in rats submitted to experimental periodontitis. For development of periodontitis, ligatures were inserted into the right and left upper second molars of rats (Rattus norvegicus, albinus, Wistar) for 15 days. Then the animals (n = 32) were randomly assigned to 2 groups: Group Test (n = 16) ligation + RESV (RESV-β-CD) and Control Group (n = 16) ligation + β-CD. Both the Test Group and Control Group animals received the daily dose of 10 mg / mL / kg of RESV-β-CD or only β-CD according to the groups for 14 and 30 days. The animals were euthanized and the jaws separated, reduced and submitted to histological processing for histological and histometric analysis. Data were submitted to Student's t-test with significance level of 5%. The values of linear measurements in the interproximal region of the cementitious enamel junction (JEC) to the alveolar bone crest (COA) demonstrated that there was a lower bone resorption in the RESV-β-CD group 14 when compared to the β-CD14 group (p = 0.001). Between the experimental times it was verified that there was a statistical difference in the Test Group (p = 0.001), and the lowest bone loss measured from the JEC to the COA was verified in the time of 14 days. According to the methodology used, it can be concluded that RESV reduced resorption in the alveolar ridge crest region in 14 days, but the use of the drug in times longer than 30 days did not favor the reabsorption of the alveolar bone crest .